2022
DOI: 10.1111/nph.18546
|View full text |Cite
|
Sign up to set email alerts
|

A phosphate starvation response‐regulated receptor‐like kinase, OsADK1, is required for mycorrhizal symbiosis and phosphate starvation responses

Abstract: Most land plants associate with arbuscular mycorrhizal (AM) fungi to secure mineral nutrient acquisition, especially that of phosphorus. A phosphate starvation response (PHR)centered network regulates AM symbiosis.Here, we identified 520 direct target genes for the rice transcription factor OsPHR1/2/3 during AM symbiosis using transcriptome deep sequencing and DNA affinity purification sequencing. These genes were involved in strigolactone biosynthesis, transcriptional reprogramming, and bidirectional nutrient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 51 publications
(77 reference statements)
0
10
0
Order By: Relevance
“…Among them are SL biosynthesis genes and LysM‐RLKs involved in precontact signaling, common symbiosis genes required for fungal cell entry such as SYMBIOSIS RECEPTOR KINASE ( SYMRK ), CALCIUM and CALMODULIN DEPENDENT KINASE (CCaMK ) and CYCLOPS and genes encoding nutrient transporters, which operate in nutrient exchange at the peri‐arbuscular membrane (Fig. 2a; Das et al ., 2022; Shi et al ., 2022). For the common symbiosis genes SYMRK, CCaMK, and CYCLOPS, this was confirmed in the phr1a mutant of the model legume and dicotyledon Lotus japonicus (Das et al ., 2022).…”
Section: The Role Of the Psr System In Am Symbiosismentioning
confidence: 99%
“…Among them are SL biosynthesis genes and LysM‐RLKs involved in precontact signaling, common symbiosis genes required for fungal cell entry such as SYMBIOSIS RECEPTOR KINASE ( SYMRK ), CALCIUM and CALMODULIN DEPENDENT KINASE (CCaMK ) and CYCLOPS and genes encoding nutrient transporters, which operate in nutrient exchange at the peri‐arbuscular membrane (Fig. 2a; Das et al ., 2022; Shi et al ., 2022). For the common symbiosis genes SYMRK, CCaMK, and CYCLOPS, this was confirmed in the phr1a mutant of the model legume and dicotyledon Lotus japonicus (Das et al ., 2022).…”
Section: The Role Of the Psr System In Am Symbiosismentioning
confidence: 99%
“…Recently, significant portions of the AMF genetic network were revealed to be under control of the phosphate-stress-responsive PHR-SPX system, which is conserved in Arabidopsis (Shi et al, 2021; Shi et al, 2022). In Arabidopsis , PHR also regulates the microbiome by reducing plant defenses when phosphate is low, resulting in recruitment of beneficial microbes (Finkel et al 2019, Martin-Rivilla et al 2019, Castrillo et al 2017,Cho, Kang, and Kim 2013; Kotchoni and Gachomo 2006; Dangl 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Shi et al . (2022), showed that the expression of the MtKIN3 homolog OsARK1 is regulated by PHRs in rice, further indicating crosstalk between nitrogen and Pi signaling.…”
Section: Nitrogen and Phosphorus Coregulationmentioning
confidence: 98%
“…Recent studies in M. truncatula showed that kin3 mutants display a much lower mycorrhizal infection rate than the wild-type under high-nitrogen conditions, while root colonization under low-nitrogen conditions was not affected, indicating that it plays a role in adjusting the symbiotic response according to soil nitrogen levels (Irving et al, 2022). Interestingly, Shi et al (2022), showed that the expression of the MtKIN3 homolog OsARK1 is regulated by PHRs in rice, further indicating crosstalk between nitrogen and Pi signaling.…”
Section: Regulation Of the Mycorrhizal Symbiosismentioning
confidence: 99%
See 1 more Smart Citation